Improving community skills through environmentally friendly ecoprinting techniques in Keude Birem Village - Ahmad Ridha; Nur Ismanidar; Salman Syarief (Universitas Muhammadiyah Magelang, 2024)
The community of Keude Birem Village lacked sufficient skills and knowledge in ecoprinting, a natural dyeing method using leaves and flowers. This limited economic opportunities and awareness of environmental conservation through the utilization of local resources. Therefore, this community service program aimed to enhance the skills and knowledge of Keude Birem villagers in ecoprinting techniques and introduce appropriate technology to improve efficiency and productivity. The training involved two main techniques: ecoprint pounding and steaming, along with the introduction of a simple steaming device. Participants were trained to create various ecoprinted products on fabric and bags, utilizing local resources such as mangrove, mango, and teak leaves. The program resulted in improved technical skills among participants, leading to higher-quality ecoprinted products with increased market value, enhanced production efficiency, and heightened awareness of environmental conservation through the sustainable use of natural dyes and local resources.